Efficacy and Safety of Modified Dual Therapy as the First-line Regimen for the Treatment of Helicobacter pylori Infection: A Meta-Analysis of Randomized Controlled Trials. Issue 10 (November 2021) - Huang, Qiuyue; Shi, Zongming; Cheng, Hong; Ye, Hui; Zhang, Xuezhi
Abstract : Background: In an era of antibiotic resistance, modified dual therapy has been paid much attention because of simple drug composition and low resistance of amoxicillin. However, its eradication rate as a first-line regimen remains controversial. This study is to evaluate the efficacy and safety of modified dual therapy for the initial treatment of Helicobacter pylori ( H. pylori ) infection compared with mainstream first-line therapies. Methods: PubMed, the Cochrane Library, and Embase were searched for randomized clinical trials evaluating the efficacy and safety of modified dual therapy as the initial treatment for H. pylori eradication compared with guideline-recommended first-line therapies. A meta-analysis was conducted using Review Manager 5.3 and dichotomous data were estimated by the risk ratio (RR) with the 95% confidence interval (CI). We also performed subgroup analysis according to control groups and studies with antibiotic susceptibility tests. Results: Eight studies including 1672 patients with H. pylori infection met the selection criteria and were assessed. The meta-analysis demonstrated that modified dual therapy achieved similar efficacy [85.83% vs. 86.77%, RR 0.99 (95% CI, 0.95-1.03), intention-to-treat analysis; 89.53% vs. 90.45%, RR 0.99 (95% CI, 0.96-1.02), per-protocol analysis] and compliance [95.77% vs. 95.56%, RR 1.00 (95% CI, 0.98-1.02)] compared with recommended first-line regimens. In addition, there were no significant differences in comparing the eradication rate of modified dual therapy with clarithromycin triple therapy, bismuth quadruple therapy, and concomitant therapy, respectively. Subgroup analysis based on the studies with antibiotic susceptibility tests also confirmed a similar efficacy. However, modified dual therapy showed fewer adverse effects [8.70% vs. 22.38%, RR 0.39 (95% CI, 0.28-0.54)], with a significant difference ( P <0.00001). Conclusion: Modified dual therapy achieved equal efficacy and compliance compared with recommended first-line regimens for H. pylori infection, and generally modified dual therapy showed fewer side effects. Abstract : Supplemental Digital Content is available in the text.